Estimation of nitrogen transforming microorganisms in soils of different tea valleys of Bangladesh - Gafur, MA; Sultana, Afroza (Bangladesh Journal of Botany, 2013)
Physico-chemical properties of soils and quantitative estimation and distribution of population of Azotobacter, ammonifying, nitrifying and denitrifying bacteria in soils under tea plants of tea valleys of Bangladesh were studied. Soil texture ranged from loam to clay loam, pH ranged from 4.84 - 5.65 and organic carbon varied between 0.18 and 2.12%. Population of Azotobacter, ammonifying bacteria, Nitrosomonas, Nitrobacter and denitrifying bacteria ranged from 18.0 × 109/g - 88.4 × 109cfu/g soil, 0.20 × 109/g - 0.24 × 109/g soil, 0.20 × 109/g - 0.24 × 109/g soil, 0.20 × 109/g - 0.24 × 109/g soil and 0.17 × 109/g - 0.24 × 109/g soil, respectively. The populations of microorganisms were not related with soil pH and organic carbon. Ammonifying bacteria was positively and significantly correlated with Nitrosomonas and Nitrobacter and Nitrosomonas with Nitrobacter at 0.01% level. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15907 Bangladesh J. Bot. 42(1): 161-165, 2013 (June)